INVESTIGATING THE INTERPLAY OF ETHICAL LEADERSHIP AND SLEEP QUALITY IN SHAPING EMPLOYEE SERVICE INNOVATION BEHAVIOR: A DUAL-PATH MODELANALYSIS - I Dewa Gede Sayang Adi Yadnya; Abdul Wahab Syakhrani; Haryanti; Henny Noviany; Eliagus Telaumbanua (Adisam Publisher, 2024)
This study investigates the dynamic interplay between ethical Leadership, sleep quality, and employee service innovation behavior within organizational contexts. Employing a dual-path model analysis, we explore how ethical leadership practices influence service innovation and how sleep quality moderates this relationship. The research in diverse industries integrates quantitative survey data and draws upon organizational behavior theories to unravel the intricate dynamics shaping contemporary workplace environments. Anticipated findings reveal a substantial positive correlation (approximately 85%) between ethical Leadership and service innovation. Additionally, the study uncovers the nuanced conditions under which sleep quality amplifies or diminishes the positive effects of ethical Leadership on employee service innovation behavior. This research contributes theoretical advancements to dual-path models and offers practical implications for organizational strategies, emphasizing ethical leadership development and sleep quality improvement. Future research directions include longitudinal exploration, cross-cultural analyses, and intervention studies, while ethical considerations prioritize participant well-being and informed consent.